Teaching Methodology of Specialty Chinese Based on Smart Class: A case study of legal Chinese - MA, Linlin (Sinología hispánica. China Studies Review, 2020)
Through the analysis of the changes of classrooms and classes of Chinese and the characteristics of the information age, relying on smart classroom and mind map, the author takes the teaching method for legal Chinese as a case, to explore the smart teaching during the stage of specialty Chinese teaching. Moreover, through the study of the characteristics of legal Chinese, this article also discusses the characteristics and difficulties in the preparation of the specialty Chinese textbook with legal Chinese as an example and the countermeasures for them. In this article, the author introduces the student language questionnaire, and based on the data analysis of the language questionnaire, tries to summarize the factors influencing the students' language learning process and the method of applying the factors to the preparation of the specialty Chinese textbook.